Ozone: An adjunct in dental treatment - Poulami Goswami; Kanchan Sharma; Niladri Maiti; Sweta Yadav; Vartika Verma; Rahul Puthenkandathil (Journal of Pharmacy and Bioallied Sciences, 2024)
Ozone is utilized in dentistry as ozonated oils, ozonated water, and gaseous ozone. The application of ozone in all specialties of dentistry has been demonstrated to be biocompatible. It has been demonstrated to encourage the remineralization of recently carious teeth, and it is utilized in dental caries and intracanal irrigants in endodontic treatment. Herpes virus infection, avascular osteonecrosis of the jaw, and alveolitis have all been treated with it. It can be applied as a supplement in the surgical and ongoing stages of periodontal disease and also hinders plaque formation. The purpose of the present review article is to discuss the numerous application of ozone in dentistry.